2013
DOI: 10.1142/s0219519413500462
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anterior Cruciate Ligament Reconstruction With Lars Artificial Ligament: An 8–15-Year Follow-Up

Abstract: The aim of this study was to evaluate the clinical results of anterior cruciate ligament (ACL) reconstruction with an artificial ligament of the Ligament Augmentation and Reconstruction System (LARS) via an 8–15-year follow-up. Between January 1996 and January 2003, 38 patients received arthroscopic anterior cruciate reconstruction with the LARS artificial ligament at the Show Chwan Memorial Hospital, Changhua, Taiwan. Among them, 28 cases were included in this study. Excluding two failure cases, 26 cases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Grafts were ruptured in 1 patient and abraded in the other, and the position of the femoral tunnel was not ideal in both patients. Wang et al 56 also reported 2 cases of synovitis in their long-term follow-up. In the present study, synovitis was observed in 1 patient with synthetics, secondary to a graft rupture.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Grafts were ruptured in 1 patient and abraded in the other, and the position of the femoral tunnel was not ideal in both patients. Wang et al 56 also reported 2 cases of synovitis in their long-term follow-up. In the present study, synovitis was observed in 1 patient with synthetics, secondary to a graft rupture.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, these synthetics, claimed as new-generation devices by manufacturers and clinical believers, showed satisfactory shortterm and midterm outcomes, 18,20,34,41,44 while the longterm outcomes were inconsistent. 22,45,53,56 Sports medicine has been developing fast in China for the last decade. ACL reconstruction now can be routinely performed for the ACL-injured athletic population in most regions of the country.…”
mentioning
confidence: 99%
“…Although the LARS ligament has been used for ACL reconstruction since the late 1990s, there are very few studies that analyzed the long-term results and sometimes the reported data are discordant. 18 19 20 21 Cerulli et al 18 reported the results obtained with the use of LARS ligament in ACL reconstruction in a group of 25 patients after 9 years of follow-up. The authors reported satisfactory results in over 95% of the cases with no cases of knee synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a failure rate of 4.4%, and an overall complication rate of 2.2% with 86.6% of the patients returning to their sports activities. Wang et al 20 reported on 26 cases of ACL reconstruction with LARS after a mean follow-up of 11.9 years. The authors reported a complication rate of 28.6% with two cases of knee synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…As these authors note, synthetic ACL substitutes have historically had unacceptably high failure rates. The specific device that they used has generated acceptance among some surgeons 2,3,10,18,32 but also several unfavorable reports of frequent failures 12,30,33 and sporadic cases of intense synovitis 10,11,32 or foreign-body reaction. 31 The current authors attribute their success with the synthetic device to the strict requirement for remnant preservation and careful attention to tunnel positioning.…”
mentioning
confidence: 99%